2021
DOI: 10.3390/plants10081542
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy and Machine-Learning for Early Detection of Bacterial Canker of Tomato: The Asymptomatic Disease Condition

Abstract: Bacterial canker of tomato is caused by Clavibacter michiganensis subsp. michiganensis (Cmm). The disease is highly destructive, because it produces latent asymptomatic infections that favor contagion rates. The present research aims consisted on the implementation of Raman spectroscopy (RS) and machine-learning spectral analysis as a method for the early disease detection. Raman spectra were obtained from infected asymptomatic tomato plants (BCTo) and healthy controls (HTo) with 785 nm excitation laser micro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…In particular, a reduced concentration of carotenoids in grapevine suggests a functional link to either a modulation of transcripts involved in carotenoid metabolism or to their degradation and fragmentation or conversion to apocarotenoids, i.e., signaling molecules produced in response to stress. A decrease in carotenoid concentration has been frequently reported when analyzing by Raman spectroscopy plants infected by pathogens ( Dou et al, 2021 ; Farber et al, 2021 ; Vallejo-Pérez et al, 2021 ) or subjected to abiotic stresses ( Altangerel et al, 2017 ; Sng et al, 2020 ), confirming the role of this class of molecules in plant stress responses.…”
Section: Resultsmentioning
confidence: 56%
“…In particular, a reduced concentration of carotenoids in grapevine suggests a functional link to either a modulation of transcripts involved in carotenoid metabolism or to their degradation and fragmentation or conversion to apocarotenoids, i.e., signaling molecules produced in response to stress. A decrease in carotenoid concentration has been frequently reported when analyzing by Raman spectroscopy plants infected by pathogens ( Dou et al, 2021 ; Farber et al, 2021 ; Vallejo-Pérez et al, 2021 ) or subjected to abiotic stresses ( Altangerel et al, 2017 ; Sng et al, 2020 ), confirming the role of this class of molecules in plant stress responses.…”
Section: Resultsmentioning
confidence: 56%
“…In the PC image, pixels of similar values (scores) are similar in terms of the different components (here, Raman spectral peaks corresponding to different cell wall polymers) contributing to the loading vector of the PC considered. A Whittaker curve [log (eigenvalues) = principal component numbers] was calculated in order to determine the number of eigenvalues necessary to explain around 95% of the variance ( Zhang et al, 2017 ; Vallejo-Pérez et al, 2021 ). In our case the curve indicated that the first six PCs should be imaged.…”
Section: Methodsmentioning
confidence: 99%
“…But it has not been applied in the manner in which we describe- a human finger’s vasculature when looked at transcutaneously and non-invasively. Moises Roberto Vallejo-Perez et al applied the classifier algorithms multilayer perceptron and linear discriminant analysis for “early detection of bacterial canker of tomato” (10). Lihao Zhang et al applied a support vector machine (SVM) analysis for the “classification of breast cancers’’ (11).…”
Section: Introductionmentioning
confidence: 99%